ANALISIS KEBIJAKAN PEMBATASAN SOSIAL BERSKALA BESAR DALAM PENANGGULANGAN CORONAVIRUS DISEASE 2019 (COVID-19) DI KOTA BOGOR - Ulfa, Annisa Sayyidatul (Journal of Indonesian Health Policy and Administration, 2021)
Pembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: Pembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively. Keywords: COVID-19, Policy, PSBB, Policy Triangle Analysis, SWOPembatasan Sosial Berskala Besar (PSBB) is a policy needed by Bogor City's people to prevent the spread of COVID-19. In its implementation, Bogor City conducted 5-stage of PSBB. This policy provides an overview to stakeholders regarding evaluation, Analysis of strengths, weaknesses, opportunities, and threats, as well as recommendations for PSBB policies in Bogor City. This study uses a Rapid Analysis approach with Media Content Analysis on various policies made by its Government regarding PSBB published from April 13 - June 25, 2020. Data analysis uses a policy triangle and a SWOT model. Policy actors issued 18 health, socio-economy, education, transportation, employment, and religion regulations. At the same time, the content consists of guidelines for implementing PSBB in various sectors such as public places/facilities, educational institutions, workplaces, health facilities, places of worship, transportation facilities, markets/shopping centers, punishment for PSBB violations, as well as content regarding the extension of the PSBB itself. The response of the Bogor City Government to the COVID-19 pandemic was excellent and fast. However, many violations have occurred in the implementation even though there has been punishment. Lack of policy control, low community compliance, and lack of infrastructure can interfere with the implementation of PSBB. There is a need for the cooperation of all parties so that PSBB can run effectively.